Occupational Noise Exposure in Open-Pit Coal Mining: Implications for Auditory Health, Safety Risks, and the Need for Real-Time Monitoring - Adenan, Adenan; Yamin, Imam Syahputra (Rifa'Institute, 2026)
Introduction: Noise is a dominant physical hazard in the mining industry that is often overlooked, despite its significant impact on auditory health and occupational safety risks, including fatigue and accidents. Objective: This study aims to identify the profile of noise exposure, analyze its impact on workers' hearing function and safety risks, and formulate optimal control strategies at a major coal mining services company. Methods: A descriptive observational case study was conducted in August 2025 at critical operational areas (Pit Road and Workshop). Primary data were collected using a calibrated Sound Level Meter referring to SNI 7231:2009 standards, while secondary data were obtained from workers' audiometric Medical Check-Up (MCU) results. Results and Discussion: Measurements indicated that 80% of sample points exceeded the Threshold Limit Value (85 dBA), with the highest intensity reaching 98 dBA in the Workshop area. MCU analysis revealed a prevalence of hearing impairment indications of 35% among operators with a service period of >5 years. High noise levels were also identified as potential factors reducing vigilance and hindering operational communication. Conclusion: Current administrative controls and the use of Personal Protective Equipment (PPE) are insufficient in reducing risks. The study recommends a transition towards technology-based continuous noise monitoring (IoT) and the integration of health data for more proactive OHS risk management